MENGENAL SEMIOTIKA DESAIN KOMUNIKASI VISUAL - Murtono, Taufik (Capture : Jurnal Seni Media Rekam, 2010)
Whether semiotics can be classified as "science"? As an analytical tool that examines culture, semiotics is not always seen as "science". Most experts in the field of view of semiotics semiotics theory only as a tool to study the sign, namely as a system of living in a culture. However, there is also regarded semiotics as a science because it can show itself as an independent discipline. Already have a methodological tool derived from the theory. It can produce a number of hypotheses. It can be used to predict, and its findings provide the possibility to change the view of the objective world.Keyword: Semiotics, science, visual communications